“The most prominent and at the same time most harmful”: D. D. Bokhan in Wilno (1921–1923) - Lavrinec, Pavel (Literatūra, 2019)
Publicist, editor of periodicals, translator of Polish poetry, literary critic Dorofey Bokhan is an outstanding member of the Russian literary life of Minsk and Wilno. His biography in the Minsk period before the turn of 1919 and 1920 is generally well-known. But the Wilno period (1921–1939) has not been studied enough. The purpose of the study is to reconstruct the activities of Bokhan in Wilno in the first years after fleeing from the Bolshevik Minsk. The material for this study are newspapers in Russian, as well as documents of the Office of Government Commissar for the City of Wilno, Starostwo of Wilno and other institutions stored in the Lithuanian Central State Archives. The documents reveal a confusion about Bokhan’s year of birth: in some documents 1872 is indicated, in others – 1878. On the other hand, the date of Bokhan’s appearance in Wilno is discovered: he was registered at a new address on January 7, 1921. On the same day an edition of “Vilenskoe slovo” was released that included Bokhan’s first publication. Bokhan published articles, reviews, translations of Polish poetry in this newspaper. He also translated a poem by a young Belarusian poetess Natalia Arsenyeva and excerpts from the poem by a classic of Lithuanian literature Maironis “Young Lithuania”, as well as a poem by a Lithuanian poet Matas Grigonis. Bokhan translated Lithuanian poetry into Russian from Polish translations. Some of his articles were signed by the initials D. B., in some cases – N. Serebryansky. Feuilletons and poetic feuilletons were signed by the pseudonym Dodo and Vova Krutikov. The publication of the newspaper “Vilenskoe slovo” ceased in August 1921. In October of the same year, the “Vilenskoe utro” newspaper began to be published. The role of Bokhan in the newspaper was so great that the authorities considered him the actual editor, not the nominal editor Anatoly Romashev. In 1921, Bokhan became one of the leaders of the Wilno Russian society and headed the Literary and artistic section of the society. The literary and artistic section held numerous literary evenings. The authorities were suspicious of the patriotic character of the evenings. Reports on Russian culture were presented as a manifestation of disloyalty to the Polish state. The authorities saw Bokhan as “the most prominent and at the same time harmful” leader of the Russian press and the Wilno Russian society. Thus, in the early years of Bokhan in Wilno, he occupied an important place in the local Russian press and began to play a key role in Russian literary life. But due to conflicts in the Wilno Russian society in 1923, he withdrew from the society’s board and withdrew from participation in the Literary and artistic section.